2020
DOI: 10.48067/ijal.827568
|View full text |Cite
|
Sign up to set email alerts
|

Lise Öğrencilerinde Sosyal Görünüş Kaygısı ve Fiziksel Aktiviteye Katılım Motivasyonu İlişkisi

Abstract: Bu araştırmanın amacı, lise öğrencilerinin sosyal görünüş kaygısı ve fiziksel aktiviteye katılım motivasyonu düzeylerini bazı değişkenlere göre incelemek ve aralarındaki ilişkiyi belirlemektir. Araştırmanın çalışma grubunu, Ağrı ve Erzincan illerinde yer alan liselerde öğrenim gören 337 kız öğrenci oluşturmaktadır. Veri toplama aracı olarak "Sosyal Görünüş Kaygısı Ölçeği (SGKÖ)" ve "Fiziksel Aktiviteye Katılım Motivasyonu Ölçeği (FAKMÖ)" kullanılmıştır. Verilerin analizinde; betimsel istatistik yöntemler, t-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
1
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
2
1
1
2
Order By: Relevance
“…In the study, it was found that father's education level and mother's education level did not reveal a significant difference with social appearance anxiety. This result was reported by Küçük Kılıç 26 , Çetinkaya et al 21 , Alımcı 27 , Şahin 28 , Dinç Altun 23 and Şahin, Barut and Ersanlı 29 research findings.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In the study, it was found that father's education level and mother's education level did not reveal a significant difference with social appearance anxiety. This result was reported by Küçük Kılıç 26 , Çetinkaya et al 21 , Alımcı 27 , Şahin 28 , Dinç Altun 23 and Şahin, Barut and Ersanlı 29 research findings.…”
Section: Discussionsupporting
confidence: 74%
“…Şahin 31 determined that there was no significant difference between middle school student's social appearance anxiety levels depending on the age variable. Similarly, studies conducted on adolescents have shown that age does not have a significant effect on social appearance anxiety 25,26,27,30,32,33,34,35,36,39,40 .…”
Section: Discussionmentioning
confidence: 93%
“…According to this, it was determined that high school students use environmental and causal motivation sources more in participation in physical activity. Unlike this study, as a result of his study, Kılıç (2020) stated that the motivations for participation in physical activity did not differ significantly according to the class variable.…”
Section: Discussioncontrasting
confidence: 72%
“…As a result of this study, which tried to determine the relationship between the digital game addiction levels of secondary and high school students during the pandemic process and their motivation for participation in physical activity, it was observed that the motivation of the students to participate in physical activity was high and their digital game addiction was low when the average scores of the scale were examined. As a result of the literature review, similar to this study, Öncel and Tekin (2015) stated that the average of computer game addiction among students is not high in general; Kılıç (2020) stated that participants' perceptions of motivation for participation in physical activity are above the moderate level; on the other hand, Tekkurşun Demir and Cicioğlu (2019) stated that their students' motivation for participation in physical activity is at a high level.…”
Section: Discussionsupporting
confidence: 67%
“…Sınıf öğrencilerinden yüksek olduğu belirlenmiştir. Alanyazın tarandığında, farklılaşmanın olduğu (Aktaş, 2020;Güvenen, 2017) ve olmadığı çalışmalara rastlanmak mümkündür (Kılıç Küçük, 2020;Ökten, 2019;Soylu ve ark., 2017). Örneğin, yapılan bir araştırmada sosyal görünüş kaygısının sınıf düzeyi değişkenine göre anlamlı şekilde Aydın ve İmir / Ergenlerin Duygusal Zeka Düzeyleri İle Sosyal Görünüş Kaygı Düzeyleri Arasındaki İlişkinin İncelenmesi / Investigation of the Relationship between Emotional Intelligence Levels and Social Appearance Anxiety Levels of Adolescents farklılaşmadığı ifade edilmiştir fakat 9.sınıfa devam eden öğrencilerin sosyal görünüş kaygı toplam puanlarının diğer sınıflarda yer alan öğrencilere göre daha yüksek bulunmuştur (Çakmak ve Sakarya, 2020).…”
Section: Discussionunclassified